2016
DOI: 10.2135/cropsci2015.05.0312
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Fusarium Head Blight Resistance Quantitative Trait Loci in Winter Wheat Cultivar NC‐Neuse

Abstract: Fusarium head blight (FHB), primarily caused by Fusarium graminearum, can significantly reduce the grain quality of wheat (Triticum aestivum L.) due to mycotoxin contamination. The objective of this study was to identify quantitative trait loci (QTL) for FHB resistance in the moderately resistant soft red winter wheat cultivar NC‐Neuse. A total of 170 recombinant inbred lines (RILs) from a cross between NC‐Neuse and the susceptible cultivar AGS 2000 were evaluated in inoculated, mist‐irrigated field nurseries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 56 publications
4
39
2
Order By: Relevance
“…nc-6A.3 from the present study overlapped with the QTL regions Q fhb.nc-1A, Q fhb.nc-4A, and Q fhb.nc-6A identified in the NC-Neuse ´ AGS 2000 population (Petersen et al, 2016) (Fig. nc-6A.3 from the present study overlapped with the QTL regions Q fhb.nc-1A, Q fhb.nc-4A, and Q fhb.nc-6A identified in the NC-Neuse ´ AGS 2000 population (Petersen et al, 2016) (Fig.…”
Section: Linkage Map For Bess ´ Nc-neuse Doubled Haploid Populationsupporting
confidence: 66%
See 2 more Smart Citations
“…nc-6A.3 from the present study overlapped with the QTL regions Q fhb.nc-1A, Q fhb.nc-4A, and Q fhb.nc-6A identified in the NC-Neuse ´ AGS 2000 population (Petersen et al, 2016) (Fig. nc-6A.3 from the present study overlapped with the QTL regions Q fhb.nc-1A, Q fhb.nc-4A, and Q fhb.nc-6A identified in the NC-Neuse ´ AGS 2000 population (Petersen et al, 2016) (Fig.…”
Section: Linkage Map For Bess ´ Nc-neuse Doubled Haploid Populationsupporting
confidence: 66%
“…Recently, quantitative trait loci (QTL) conferring FHB resistance were mapped in the cultivars NC-Neuse (Petersen et al, 2016) and Truman (Islam et al, 2016). Identification and mapping of QTL in US sources of resistance, as well as validation of mapped QTL, remain important research objectives for the efficient use of marker-assisted selection (MAS) (Griffey, 2005;Brown-Guedira et al, 2008).…”
Section: Validation Of Fusarium Head Blight Resistance Qtl In Us Wintmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the SNPs identified in the individual year GWAS decreased SEV in both years and could be a useful tool in selection for resistance, although their absence in the 2‐yr GWAS is not encouraging. Petersen et al (2016) identified resistant QTL on chromosomes 1A, 2A, and 6A associated with SEV in the winter wheat cultivar NC‐Neuse. Liu et al (2013) identified two QTL on chromosomes 1D and 3B that decreased SEV.…”
Section: Discussionmentioning
confidence: 99%
“…Bonin and Kolb (2009) also reported that chromosome 6B was associated with kernel damage, and Liu et al (2009) identified chromosomes 5B and 6B as important for FHB resistance breeding. In addition, Petersen et al (2016) identified chromosomes 4A and 5B, and Liu et al (2012) observed chromosome 5B to be associated with DON.…”
Section: Discussionmentioning
confidence: 99%